Clinical effect of pemetrexed as the first‐line treatment in Chinese patients with advanced anaplastic lymphoma kinase‐positive non‐small cell lung cancer. Issue 4 (11th May 2016) - Ma, Di; Hao, Xuezhi; Wang, Yan; Xing, Puyuan; Li, Junling
Abstract : Background: The efficacy of pemetrexed‐based first‐line chemotherapy in anaplastic lymphoma kinase (ALK)‐positive non‐small cell lung cancer (NSCLC) has been demonstrated in several studies; however, there is a lack of data from Chinese populations. Methods: The clinicopathological characteristics and treatment outcomes of 52 patients with ALK‐positive advanced NSCLC who received pemetrexed as first‐line chemotherapy at the Department of Medical Oncology, Cancer Hospital, Chinese Academy of Medical Sciences were retrospectively reviewed. The primary end points were response rate and progression‐free survival (PFS). Results: The gender proportion was balanced and the median age was 51 years (range 26–76). Of the 52 patients, 46 (88.5%) had stage IV disease, predominantly adenocarcinoma (98.1%). Sixteen patients were current/former smokers and 36 were never/light smokers. The most common sites of metastasis were the pleura (36.5%), bone (30.8%), lung (26.9%), and brain (17.3%). The median PFS was 9.5 months (95% confidence interval 7.454–11.536). At the time of analysis, partial remission was achieved in 18 (34.6%) patients, stable disease in 26 (50.0%), and progressive disease in eight (15.4%); none of the patients achieved complete remission. The objective response rate was 34.6% and the disease control rate was 84.6%. Common adverse events with pemetrexed were neutropenia (53.8%), nausea and vomiting (51.9%), leukopenia (32.7%), and fatigue (25.0%), mainly at grades 1 or 2. Conclusions: Pemetrexed is efficient and tolerated as first‐line treatment for ALK‐positive NSCLC in a cohort of Chinese patients and may prove to be an alternative option for the treatment of ALK‐positive NSCLC.